2017
DOI: 10.21093/ijeltal.v2i1.44
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Self Regulated Strategy Development on Students’ Skill to Write Persuasive Text

Abstract: Abstract:Writing is one of the four skills taught in the school which is used as communication in daily life. It is considered as a difficult subject by the eleventh grade of the senior high school students because of the limitation of the time provided and some aspects of language to be considered. Therefore, the purpose of this study was to find out whether or not there was a significant difference in students' writing achievement of persuasive text between the students who were taught by using Self-Regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The teacher might use social media like Facebook to teach writing (Annamalai, 2017), or using Self Regulated Strategy (Sartika & Rachmanita, 2017), or implement Collaborative Writing on Google Docs (Valizadeh, 2022). One of the most important keys and successful ways to enhance the students writing is when the student has a difficulty in writing, the English teacher should find a solution to solve it (Setyowati et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The teacher might use social media like Facebook to teach writing (Annamalai, 2017), or using Self Regulated Strategy (Sartika & Rachmanita, 2017), or implement Collaborative Writing on Google Docs (Valizadeh, 2022). One of the most important keys and successful ways to enhance the students writing is when the student has a difficulty in writing, the English teacher should find a solution to solve it (Setyowati et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…One notable exception is Self‐Regulated Strategy Development (SRSD: Harris, Schmidt, & Graham, 1998), an intervention that teaches students composition strategies while also developing positive attitudes about writing. Many studies have demonstrated the efficacy of SRSD in students with and without diagnosed disabilities (Alharbi, Hott, Jones, & Henry, 2015; Mason et al., 2017; Sartika & Rachmanita, 2017). While the current study did not find systematic differences in behavior between students who are AR‐WD and students who are TDW, there were multiple instances across both groups where the percentage of students with behaviors in the clinical range (above one standard deviation) exceeded normal expectations (16 percent).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, each of the above–named studies looked at SLDs across impairment without examining how SLD–reading, writing, or math might differentially relate to behavior. More recently, Sainio, Eklund, Ahonen, and Kiuru (2019) reported a significant relation between academic emotions and reading and math disabilities in sixth grade students. Here, students with reading disabilities showed lower levels of hope and higher anxiety toward reading than those without reading disabilities, while students with math disabilities showed lower enjoyment, lower hope, and higher levels of anxiety than students without math disabilities.…”
Section: Specific Learning Disabilities and Social–behavioral Difficu...mentioning
confidence: 98%
“…Students tend to have good ideas from reading when they are going to write down these ideas. Besides, students had experience difficulties such as unclear writing content, inaccurate word choices, and less variety of words and sentences (Sartika & Rachmanita, 2017). In short, writing is the most difficult language skill because writing is not recording vocabulary of the text but elaborating and pouring ideas into an orderly writing structure.…”
Section: Introductionmentioning
confidence: 99%